DICER1-Mutated Botryoid Fibroepithelial Polyp of the Parotid Duct: Report of the First Case - Erber, Ramona; Preidl, Raimund; Stöhr, Robert; Haller, Florian; Hartmann, Arndt; Kesting, Marco Rainer; Agaimy, Abbas (Head and Neck Pathology, 2021)
DICER1, a member of the ribonuclease III family, is involved in the biogenesis of microRNAs and, hence, it influences gene expression regulation. DICER1 germline (associated with the inherited DICER1 syndrome) or somatic mutations have been linked to tumorigenesis in histogenetically diverse benign and malignant neoplasms in different organs including pleuropulmonary blastoma, cystic nephroma, embryonal rhabdomyosarcoma, nasal chondromesenchymal hamartoma, poorly differentiated thyroid carcinoma, thyroblastoma, intracranial sarcoma and gonadal Sertoli-Leydig cell tumors in addition to others. Moreover, rare botryoid (giant) fibroepithelial polyps may harbor this mutation. Herein, we describe the first reported case of a DICER1-mutated botryoid fibroepithelial polyp occurring within the parotid duct of a 65-year-old female who has no other features or family history of the DICER1 syndrome. Based on its distinctive morphology, we tested this lesion specifically for DICER1 mutations and confirmed the presence of a pathogenic DICER1 variant with a low allele frequency, consistent with a somatic mutation.
CRIS-Team WoS Importer:2021-07-30